Significant adhesion reduction and time saving in pediatric heart surgery with 4DryField PH: A retrospective, controlled study - Cesnjevar, Robert; Purbojo, Ariawan; Haake, Claas; Laas, Joachim (PLoS ONE, 2022)
Adhesions formation after surgery for congenital heart defects can complicate follow-up procedures due to bleeding from detached adhesion bands, injury to cardiac structures or large vessels, all of which do prolong operation times. The problem is enhanced by the fact that detached adhesions are predilection sites for new adhesions setting off a downward spiral. 4DryField® PH gel barrier has demonstrated high efficacy in reducing postoperative adhesions in general surgical and gynecological studies. This retrospective controlled study of 22 patients evaluates whether these positive results can be confirmed in pediatric cardiac surgery. Adhesions were scored from photographs of follow-up interventions by an independent cardiac surgeon blinded to group assignment. The publication provides not only score numbers but also original photographs of all sites for better traceability and transparency. In addition, timesaving due to reduced adhesions was evaluated. Results show a significantly reduced adhesion score for the 4DryField® group. Importantly, this resulted in a significantly shorter period between skin incision and start of cardiopulmonary bypass. In addition, timesaving due reduced adhesion formation was evaluated. The use of 4DryField® was safe, although higher doses per kg were used than in adults.
CRIS-Team Scopus Importer:2022-12-02